Pandangan Gereja Katholik Terhadap Pernikahan Beda Agama (Studi Kasus Pernikahan Katholik dan Protestan di Gereja Katedral Jakarta) - Pane, Reza Hidayat (Inklusiva: Jurnal Studi Agama-Agama, 2023)
The objective of this research is to delve deeper into the perspectives of the church, specifically the Christian and Catholic churches, on interfaith marriage, with a case study focused on the Cathedral Church. This study employs a qualitative method, utilizing a sociological approach. Primary data was obtained directly through interviews conducted with figures or clergy of the Cathedral Church. The researcher employs a descriptive-analytical technique, presenting data in the form of statements or sentences that explain the core issues at hand. The findings reveal that Jakarta Cathedral Church views interfaith marriage as a sacred sacrament ideally shared between partners of the same faith. However, the church permits mixed marriages under the condition that the Catholic partner commits to maintaining their faith and raising their children in Catholic teachings. Couples must obtain a dispensation from the bishop and undergo pastoral guidance, including premarital preparation courses, to understand the spiritual and practical implications of mixed marriages.